Self-Transformation of Lay Workers through Field-Based Learning Experiences on Cancer Palliative Care - Stepanus Maman Hermawan; Hany Wihardja (GLOBAL HEALTH SCIENCE GROUP, 2025)
Palliative care is essential in improving quality of life for cancer patients, especially in community settings where access to specialist care is limited. In Indonesia, lay workers play a vital role in bridging formal health services and patients requiring psychosocial and emotional support. This study explores the self-transformation experiences of palliative care lay workers following an advanced palliative cancer training program in Jakarta. Using a qualitative approach with interpretative phenomenological analysis, the study involved 14 participants selected through purposive sampling. Data were collected via in-depth interviews and analysed thematically. Findings reveal four main themes: (1) increased confidence and competence after training, (2) challenges in implementing palliative care in the community, (3) the importance of social and institutional support, and (4) recommendations for improving future training. The study concludes that experiential, context-based training enhances lay workers’ ability to provide holistic care, though systemic support and mentorship are crucial for sustainable impact. This research contributes to the growing evidence on community lay workers in palliative care and offers insights for designing programs that empower lay workers as reliable care agents in community-based cancer management.